The Effects of Psychoeducation Intervention with Progressive Muscle Relaxation Video Therapy on Anxiety Levels in Elderly with Hypertension in Salem Village - Elma Dwi Lestari; Suci Ratna Estria (Proceedings Series on Health & Medical Sciences, 2024)
Background: Anxiety is a common reaction to situations individuals perceive as dangerous or threatening. Prolonged anxiety can disrupt a person's thoughts and behaviors. Elderly individuals often experience anxiety, primarily related to their illnesses, with hypertension being prevalent among them. The advantage of health education using video media lies in its ability to provide effective visualization to facilitate the learning process. Method: This study employed a Pre - Experimental research design with a quantitative approach, explicitly utilizing a one-group pretest-posttest design. Sampling was conducted using random sampling, with a sample size of 54 respondents. The Hamilton Anxiety Rating Scale (HARS) was used to measure anxiety. Results: The average pre-test anxiety score before the intervention was 29.79, while the average post-test score showed a decrease of 4.00, resulting in a score of 25.79. Statistical analysis using the Wilcoxon test obtained a p-value for the pre-test and post-test of 0.000 (0.050), indicating that psychoeducation intervention with PMR video therapy affected anxiety levels in the elderly with hypertension at the Salem Village Elderly Health Post. Conclusion: Psychoeducation intervention with PMR video therapy affects anxiety levels in the elderly with hypertension in Salem Village.